Nilai-nilai Budaya Minangkabau dalam Teks Pidato Batagak Gala Penghulu Karya Idrus Hakimi Datuak Rajo Penghulu - Samudro, Rio; Hamidin, Hamidin; Nurizzati, Nurizzati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study is to describe the Minangkabau cultural values ​​that exist in the text of a speech Batagak Gala Penghulu work H. Hakimy Datuak Rajo Penghulu. The data of this study is the text of a speech-based Batagak Gala Penghulu spoken text by H. Hakimy Datuak Rajo Penghulu. The data source of this research is Penghulu handbook, Bundo Kanduang and Speech Alua Pasambahan Indigenous works in Minangkabau H. Hakimy Datuak Rajo Penghulu text to speech in which there is Batagak Gala Penghulu. Data collected by reading and translating texts from Minangkabau language into Indonesian language, reading, writing, analysis, and identification. The findings of the study revealed 18 cultural values ​​that Minangkabau culture, 6 data humility and respect for others, 3 data deliberation, 3 fidelity and accuracy of data, and 5 data compliance and adherence to tradition.